The Historical Of Evaluation Program And Philosophy Assessment - Nurhayati; ambiyar; Ishak Aziz (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
This study aims to identify and understand the types of traditional instrument from West Sumatra. The method used in this study uses a library method or approach (library research). Data obtained through observation and literature study. The results showed that the historical of evaluation program called Age of Reform in 1900; the second, from 1900 until 1930, we call the Age of Efficiency and Testing; the third, from 1930 to 1945, may be called the Tylerian Age; the fourth, from 1946 to about 1957, it called the Age of Innocence; the fifth, from 1958 to 1972, is the Age of Development; the sixth, from 1973 to 1983, the Age of Professionalization; and finally the seventh from 1983 to 2000 the Age of Expansion and Integration. The philosophical foundations of evaluation and assessment include ontological, epistemological, and axiological studies. The general philosophy that forms the basis of the assessment includes idealism, realism, pragmatism, and existentialism. Meanwhile, the schools of Philosophy of Education that underlie the assessment are perennialism, essentialism, progressivism, and reconstructivism.